Clitorial inclusion cyst in an adult: a rare presentation - Huda, Tanweerul; Sutrave, Tarun; Pandya, Bharati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Dermoid cysts are benign lesions that grow slowly and can occur anywhere in the body. Clitoris is an extremely rare site for dermoids cysts. We present a case of inclusion cyst of clitoris in a middle aged woman, who had it for 10 years before presenting for relief from her symptoms. Local examination revealed a 3 cm X 4 cm size cystic mass at the clitoris giving it an appearance of clitoromegaly. She underwent an excision of the cyst at our hospital with the histopathology report suggesting the lesion to be a dermoid cyst. Postoperative recovery was uneventful with no evidence of recurrence on follow up.